2022
DOI: 10.1186/s12992-022-00883-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 on the 10-year carbon footprint of the Nagoya University Hospital and medical research centre

Abstract: Background: Amidst the climate crisis, a key goal of the medical sector is to reduce its large carbon footprint. Although the Coronavirus disease 2019 (COVID-19) pandemic greatly impacted the medical sector, its influence on carbon footprints remains unknown. Therefore, the aim of this study was to evaluate changes in the carbon footprint of a university hospital with a medical research centre over the past 10 years. Methods: Data on electricity, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…During the COVID-19 epidemic in 2021, the carbon footprint decreased slightly (January-August), probably due to the reduction in the number of workers performing faceto-face work. The results support the findings of Moroka and Raya, who indicated that the cofinancing measures imposed to reduce the impact of the pandemic had shown a considerable reduction in carbon emissions [18,19].…”
Section: Discussionsupporting
confidence: 89%
“…During the COVID-19 epidemic in 2021, the carbon footprint decreased slightly (January-August), probably due to the reduction in the number of workers performing faceto-face work. The results support the findings of Moroka and Raya, who indicated that the cofinancing measures imposed to reduce the impact of the pandemic had shown a considerable reduction in carbon emissions [18,19].…”
Section: Discussionsupporting
confidence: 89%
“…Carbon footprint is typically expressed in terms of carbon dioxide equivalent (CO 2 e), which is a unit that converts the emissions of various greenhouse gases into the equivalent amount of carbon dioxide [35,36]. This conversion allows for a standardized and comparable representation of the overall impact of different greenhouse gases on climate change.…”
Section: Carbon Footprint Calculation Methods and Data Sourcesmentioning
confidence: 99%